GRAHAM UNDERWOOD and JONATHAN PENNER, Electronic Evidence in Canada - Suderman, Jim (Archivaria, 2011)
Electronic Evidence in Canada. GRAHAM UNDERWOOD and JONATHAN PENNER. Toronto: Carswell, 2010. 340 p. ISBN 978-0-7798-2263-8.